2020
DOI: 10.1002/ddr.21754
|View full text |Cite
|
Sign up to set email alerts
|

Drug encapsulating polysaccharide‐loaded metal nanoparticles: A perspective drug delivery system

Abstract: The anticancer and antimicrobial drugs customarily suffer a functional inefficacy due to a limited delivery to the target site, active cellular efflux, in addition to the inadequacy of carrier system. Metal nanoparticles possess unique physicochemical properties as drug delivery vehicles, for delivering the drugs susceptible to cellular efflux pumps. However, a direct physiological exposure of nanoparticle surface after releasing the carrier drug poses serious concerns. The polysaccharides with enhanced biotol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Amylose when modified with ethylene diamine and poly(methyl methacrylate (PMMA) via atom transfer radical polymerization (ATRP) technique induced switchable hydrophilicity and enhanced drug complexing ability. [28] Furthermore polysaccharide-capped metal nanoparticles with special reference to Amylose have been reported by Prasher et al [29] for delivery of antibiotics and anticancer drugs which ChemistrySelect possess poor availability and degrade easily due to cellular microbial efflux. Amylopectin is a dendritic component of starch with numerous hydroxyl groups conducive to chemical modifications favoring its use in gene and drug delivery.…”
Section: Starchmentioning
confidence: 99%
“…Amylose when modified with ethylene diamine and poly(methyl methacrylate (PMMA) via atom transfer radical polymerization (ATRP) technique induced switchable hydrophilicity and enhanced drug complexing ability. [28] Furthermore polysaccharide-capped metal nanoparticles with special reference to Amylose have been reported by Prasher et al [29] for delivery of antibiotics and anticancer drugs which ChemistrySelect possess poor availability and degrade easily due to cellular microbial efflux. Amylopectin is a dendritic component of starch with numerous hydroxyl groups conducive to chemical modifications favoring its use in gene and drug delivery.…”
Section: Starchmentioning
confidence: 99%
“…Its characteristic properties such as biotolerance and nonimmunogenicity for human use, and easy availability make it a commonly used polymers/pharmaceutical excipient [254,255]. In comparison to other polymers such as gum and cellulose, starch does not need to undergo excessive purification, as they are relatively pure.…”
Section: Starchmentioning
confidence: 99%
“…Recent research has shown that the chlorotoxin (CTX) peptides increases the drug delivery efficacy together at SPION surface. [143][144][145]…”
Section: Biotherapeuticsmentioning
confidence: 99%